Enron A Select Chronology of Congressional, Corporate, and Government Activities. ([s.n.], 2002)
Provides an annotated chronology of the Enron Corp. bankruptcy and financial collapse and attendant Government investigations into and Congressional hearings regarding irregularities in accounting practices, business ethics, corporate structure, and securities matters.